2010
DOI: 10.1007/s00192-010-1310-2
|View full text |Cite
|
Sign up to set email alerts
|

Bladder mass “collagenoma”

Abstract: Large bladder masses are typically found to be malignant in nature. We present a case of a large bladder neck mass as a result of previous imprecise collagen injection for urethral bulking. The patient was successfully treated as an outpatient with transurethral excision of the collagen mass combined with post-operative anticholinergic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Other complications include temporary urinary retention, urge incontinence and transient haematuria . More rarely complications can include urethral mucosal prolapse, foreign body granulomas, bladder masses and urethral outlet obstruction . Overall, several studies have concluded that UBAs have a good safety profile, with low complication rates …”
Section: Introductionmentioning
confidence: 99%
“…Other complications include temporary urinary retention, urge incontinence and transient haematuria . More rarely complications can include urethral mucosal prolapse, foreign body granulomas, bladder masses and urethral outlet obstruction . Overall, several studies have concluded that UBAs have a good safety profile, with low complication rates …”
Section: Introductionmentioning
confidence: 99%